Clinical Hypnosis in the Treatment of Post-Menopausal Hot Flashes: A Randomized Controlled Trial - Elkins, Gary R. (2013)
OBJECTIVE: The use of estrogen and progesterone to manage vasomotor symptoms (i.e., hot flashes, night sweats) has declined due to concerns over their risks and there is an increased interest in alternate, effective, and low-risk treatments. This study reports the results of a randomized, controlled trial of clinical hypnosis in treating vasomotor symptoms among post-menopausal women. METHODS: Randomized, single-blind, controlled, clinical trial involving 187 post-menopausal women reporting a minimum of seven hot flashes per day, or at least 50 hot flashes a week at baseline between December 2008 and April 2012. Eligible participants received five weekly sessions of either clinical hypnosis or structured-attention control. Primary outcomes were hot flash frequency (subjectively and physiologically recorded) and hot flash score assessed by daily diaries at weeks 2–6, and 12. Secondary outcomes included measures of hot flash related daily interference, sleep quality and treatment satisfaction. RESULTS: In a modified intent-to-treat analysis that included all randomized participants that provided data, reported subjective hot flash frequency from baseline to week 12 showed a mean reduction of 55.82 hot flashes for the clinical hypnosis intervention (74.16%), versus a 12.89 hot flash reduction (17.13%) for the control (p<.001, 95% CI, 36.15–49.67). Mean reduction in hot flash score was 18.83 (80.32%) for the clinical hypnosis intervention as compared to 3.53 (15.38%) for the control (p<.001, 95% CI, 12.60–17.54). At 12 week follow-up, the mean reduction in physiologically monitored hot flashes was 5.92 (56.86%) for clinical hypnosis and .88 (9.94%) for the control (p<.001, 95% CI, 2.00–5.46). Secondary outcomes were significantly improved compared to control at 12 week follow-up in hot flash related interference (p<.001, 95% CI, 2.74–4.02), sleep quality (p<.001, 95% CI, 3.65–5.84), and treatment satisfaction (p<.001, 95% CI, 7.79–8.59). CONCLUSION: Compared to a structured attention control, clinical hypnosis resulted in significant reductions in self-reported and physiologically measured hot flashes as well as hot flash scores in post-menopausal women.